Knowledge management assessment in technology services the case of RCPT technology services, Inc.'s technical support group - Marco, Ronaldo Agustin Jr.; Talisayon, Serafin D. (Quezon City University of the Philippines Diliman, 2011)
The study has assessed the existing status of knowledge management in the Technical Support Group of RCPT Technology Services Inc (RCPT), a leading system integrator that adheres to ITSM (ISO/IEC 20000-1:2005) practices. The group handles the biggest clients of the company in terms of revenue. The ability of TSG to deliver its services relies heavily on the explicit knowledge and tacit knowledge of each engineer. To understand the capability of the group in terms of KM, a concrete illustration of the knowledge needs of the company was also presented. The existing practices will be analyzed in terms of stages in a Knowledge Cycle adopted from Talisayon. The framework is slightly modified to in view of the nature of the operations of TSG. At each stage, the assessment was made through the inputs gathered from the surveys of engineers and an interview conducted with the group's manager and team leaders. To give credence to the needs of the group and the importance of knowledge for the group, an interview with external groups was also conducted. These are the account managers handling the sales of the services of the groups, solution manager designing systems that the group supports, project managers that lead the groups' implementations and also the group tasked to monitor the groups' capability. The strengths and weaknesses as well as opportunities and threats was discussed and summarized in the SWOT framework. A link between the ITSM practices and KM practices was also explained since ITMS is a corporate wide directive while KM at the moment is not. The discussion is culminated by linking how the use of knowledge can benefit and affect the important metrics for the company. The analysis showed that management support is crucial in improving the KM practices in almost all the stages of the knowledge cycle. The lack of a company-wide KM strategy disjoints the TSG practices from the practices of other groups which can otherwise help in building an effective KM beyond the group itself. It was also established that KM can be used to complement the existing corporate standards on ITSM and vice-versa. The merger of the two will improve the capability of the group and may have a positive impact on the company's bottom-line.
In partial fulfillment of the requirements in TM 299.2
Thesis
Keywords: RCPT technology services, Inc; Knowledge management; Data processing service centers